Tinjauan Yuridis terhadap Tindak Pidana Penipuan dengan Penggunaan Identitas Palsu Terkait dengan Jual Beli Opak Ubi Kayu (Kajian Pasal 378 KUHP): indonesia - Billy Syahputra Alam; Marolop Butar Butar; Sebastian Tarigan Sibero; Gabriella Alensia Manihuruk (Jurnal Hukum Lex Generalis, 2024)
Criminal fraud is an unlawful act aimed at benefiting oneself or others by employing deception, a series of lies, or a false identity, as regulated in Article 378 of the Indonesian Criminal Code (KUHP). This study analyzes the criminal liability of the defendant and the judicial considerations in Decision No. 99/Pid.B/2023/Bnj, in which the defendant committed fraud by impersonating a military officer and borrowing money from the victim for an alleged investment in a cassava cracker procurement business. The victim suffered a financial loss of IDR 200,000,000, which was transferred to the account of an individual claimed to be the defendant’s wife.This research employs a normative juridical method, examining secondary legal materials such as books, legislation, online sources, interviews, and other relevant references. The study is qualitative in nature, focusing on legal norms in statutory regulations, court decisions, and societal norms. The findings indicate that the elements of fraud under Article 378 of the KUHP are fulfilled, including the presence of deception, criminal intent (mens rea), and financial harm suffered by the victim.